Prevalence of Mycoplasma hominis, Ureaplasma urealyticum, and Ureaplasma parvum detection in urine and respiratory tract samples in Hiroshima, Japan - Kayoko Tadera; Hiroki Kitagawa; Hiroyuki Kitano; Toshinori Hara; Seiya Kashiyama; Toshihito Nomura; Keitaro Omori; Norifumi Shigemoto; Michiya Yokozaki; Hiroki Ohge (Heliyon, 2023)
Background: Mycoplasma hominis, Ureaplasma parvum, and Ureaplasma urealyticum are commensal bacteria that are associated with colonization and infection of the urogenital tract. However, colonization of the respiratory tract by these microorganisms in adults has not been fully investigated. Methods: Urine and respiratory tract samples (sputum, tracheal aspirates, and bronchoalveolar lavage) of patients aged 20−80 years were analyzed to detect the presence of M. hominis, U. parvum, and U. urealyticum using a conventional PCR method. The samples were submitted to the microbiological clinical laboratory of Hiroshima University Hospital from December 1, 2021 to May 31, 2022. Results: In total, 334 urine and 238 respiratory tract samples were analyzed. The overall detection rates of M. hominis, U. parvum, and U. urealyticum were 2.9%, 1.7%, and 2.3% in male urine; 7.0%, 13.8%, and 1.9% in female urine; 2.2%, 0%, and 2.2% in male respiratory tract; and 0%, 2.0%, and 0% in female respiratory tract, respectively. In urine samples, the detection rates of M. hominis, U. parvum, and U. urealyticum were significantly higher (p < 0.001) for women (29/159; 18.2%) than for men (10/175; 5.7%); however, in respiratory tract samples, the detection rates were not significantly different (p = 0.70) between women (2/101; 2.0%) and men (5/137; 3.7%). Further, both the urine and respiratory samples of 83 patients were analyzed. Three male samples were positive for M. hominis or U. urealyticum, and M. hominis and U. urealyticum were matched in both the urine and respiratory tract samples: M. hominis (n = 1), U. urealyticum (n = 1), M. hominis + U. urealyticum (n = 1). Conclusion: M. hominis, U. parvum, and U. urealyticum were detected in the respiratory tract of not only the young patients, but also of patients aged 50−60 years. Further studies are required to understand the relationship of these microorganisms in urogenital and respiratory tract samples with extra-genital infections.